2006
DOI: 10.1111/j.1524-4725.2005.31086
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Laser Therapy for Wound Healing: Mechanism and Efficacy

Abstract: To better understand the utility of LLLT in cutaneous wound healing, good clinical studies that correlate cellular effects and biologic processes are needed. Future studies should be well-controlled investigations with rational selection of lasers and treatment parameters. In the absence of such studies, the literature does not appear to support widespread use of LLLT in wound healing at this time. Although applications of high-energy (10-100 W) lasers are well established with significant supportive literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
303
0
35

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 378 publications
(359 citation statements)
references
References 50 publications
9
303
0
35
Order By: Relevance
“…Some of the animal studies investigating the effects of LLLT on wound healing have found similar results to the ones found in the in vitro studies, ranging from decreased inflammation and increased collagen and granulation tissue in the wound bed to increased tensile strength and faster epithelization [20][21][22][23].…”
Section: Lllt-mechanism Of Action On Cellular and Tissular Levelsupporting
confidence: 65%
See 1 more Smart Citation
“…Some of the animal studies investigating the effects of LLLT on wound healing have found similar results to the ones found in the in vitro studies, ranging from decreased inflammation and increased collagen and granulation tissue in the wound bed to increased tensile strength and faster epithelization [20][21][22][23].…”
Section: Lllt-mechanism Of Action On Cellular and Tissular Levelsupporting
confidence: 65%
“…LLLT can also induce collagen synthesis and growth factor secretion. Furthermore, there is also a downregulation of the production of pro-inflammatory cytokines and cell apoptosis by LLLT [14][15][16][17][18][19][20].…”
Section: Lllt-mechanism Of Action On Cellular and Tissular Levelmentioning
confidence: 99%
“…20,21 Today, in many co un tri es ex cept Uni ted Sta tes, LLLT is wi dely used for the tre at ment of a va ri ety con diti ons inc lu ding ne u ro lo gic, den tal and der ma to logic di sor ders. 11 Du e to the exis ten ce of so me conf lic ting da ta for its ef fi cacy in wo und he a ling in ani mal 18,19,29 and hu man stu di es 20,21 the re is still no con sen sus for the ro u ti ne use of this the ra pe u tic mo da lity worl dwi de.…”
Section: Discussionmentioning
confidence: 99%
“…11 fi cult to com pa re the re sults of dif fe rent ex pe riments that used dif fe rent la ser pa ra me ters. Most LLLT re se arch stu di es, pro bably owing to cost or ava i la bi lity is su es, ha ve used he li um ne on (He Ne) la sers, but most of the ne wer stu di es are prof fe ring the ne wer Gal li um-Ar se ni de-Alu mi num (Ga-AsAl) la ser.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation